Resonant oscillation of vertical working part of conveyer-loader - I. Hevko; O. Lyashuk; M. Sokil; L. Slobodian; V. Hud; Yu. Vovk (Қарағанды университетінің хабаршысы. Физика сериясы)
The experimental equipment for testing the screw loader of bulk materials with horizontal and vertical branches was designed and manufactured, which allows to determine the process productivity and power consumption according to the developed methods. Experimental equipment is equipped with laboratory equipment, which ensures the change of investigated processes in wide ranges with high accuracy in the automated control mode with the fixation of necessary research results. On the basis of mathematical models, the dependences of the angular velocity of perturbation on the physico-mechanical and geometric parameters of the system of branches and the angular velocity of SWP are obtained. It was established that the resonance dynamic stresses at significant angular velocities exceed several times the resonant stresses of a «static elastic body» (which does not rotate), which makes it possible to take into account when choosing a dynamic coefficient of strength. With the same physical-mechanical and geometric characteristics of an elastic body, the resonance for larger values of the angular velocity of its rotation takes place for a smaller frequency of external periodic perturbation.